Lei Maria da Penha: percepções e vivências - César, Daniele Cristina Mistretta Vieira [UNESP] (2014)
This thesis aimed to examine the experiences of women in situations of violence and perception of police officers on violence against women and the implementation and effectiveness of the Maria da Penha Law in a city of São Paulo, to establish a correlation between the law and public policies applied in order to deter and minimize domestic violence against women. For this, we used the qualitative research method and the use of oral testimonies of women who have police report in the city of São Paulo. We also interviewed police officers this precinct Defense of Women. We chose to keep secret the name of the DDM because it is a city with a small population and has only one police station Defense of Women, which would generate constraints for both police officers and for the women interviewed. Other research sources used were the various theorists who study the domestic violence against women, the feminism, the social movements and the gender violence, basic to the study that we have proposed concepts. The theoretical framework associated with field research showed us that with the enactment of Law 11.340 on August 7, 2006, called the Maria da Penha Law, the issue of domestic violence against women had enormous repercussions throughout Brazilian society , but although it is a great advance in legislative advocacy of women's rights and insert them as subjects of rights, it is impaired at several points , the lack of public policies that make the rights and guarantees provided by law into a reality for women in situations of domestic violence. This research also revealed the need for greater awareness of women's rights in educational campaigns, it is not enough that we have laws to prevent domestic violence against women, if not educate our boys and girls so that there is a decrease of asymmetrical relations between men and women in our country and the world.